Distribution of Longidoridae in the Viticultural Regions of the Cape Province - Malan, A.P.; Meyer, A.J. (South African Journal of Enology and Viticulture, 2017)
Soil samples from five viticultural regions in the Cape Province were analysed for the presence of longidorid nematodes. Sixteen species of Xiphinema were found, the most common species being X. elongatum, X. americanum and X. brevicolle. X. index was recorded from three of the five regions. A survey in the Theewaterskloof area was conducted and nine Xiphinema species were recorded but X. index was absent.